Scientific and technological agreements for international cooperation (STAIC): A study of its generic structure potential - Coelho, Adriane Marie; Kovaleski, Nadia Veronique Jourda; Gaia, Silvia (The ESPecialist, 2021)
Internationalization is an important strategy for the participation of Higher Education institutions in the process of globalization. The academic community has sought a better understanding of its workings. It is well known that the actions that make up our lives, which include texts such as the international cooperation among universities, are partially constituted by different genres. However, due to the scarce number of textual genres analyzed in this area, there is a growing need to investigate them. In this work, 10 STAICs were used in order to investigate the Generic Structure Potential (Hasan, 1985, 1996, 2004). The selection was based on samples of STAICs from Federal, State and Private Brazilian Higher Education institutions. The results show that the STAICS are an administrative genre that presents obligatory and optional elements in its Generic Structure Potential. This study may be relevant for all areas of knowledge, in special Education, Linguistics.